Efektivitas Pelayanan BPJS Kesehatan di Mal Pelayanan Publik Kabupaten Sleman - Baselius Afrendi; Fikrin; Fera Arista Wardani; Agus Ferianto (Jurnal Masyarakat dan Desa, 2025)
This study aims to analyze the effectiveness of BPJS Health services at the Public Service Mall (MPP) in Sleman Regency as part of an integrated public service innovation. The research was motivated by the observed low service utilization and limited operational presence of BPJS Health at the MPP, raising concerns regarding service effectiveness. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and documentation. The findings reveal that BPJS Health services at MPP Sleman have not functioned effectively, as assessed using four indicators: accuracy of program targeting, effectiveness of public outreach and socialization, achievement of service objectives, and the absence of regular monitoring and evaluation. The main contributing factors include the limited availability of service personnel, low daily visitor numbers, and a shift in public preference toward digital channels and mobile-based services such as Mobile Customer Service (MCS). The study recommends a comprehensive evaluation of the BPJS Health service model at MPP to better align with current public needs and behaviors